2020
DOI: 10.3390/ijms21155256
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Pre-Conditioning Affects the Paracrine Role of Circulating Angiogenic Cells Ex-Vivo

Abstract: In atherosclerosis, circulating angiogenic cells (CAC), also known as early endothelial progenitor cells (eEPC), are thought to participate mainly in a paracrine fashion by promoting the recruitment of other cell populations such as late EPC, or endothelial colony-forming cells (ECFC), to the injured areas. There, ECFC replace the damaged endothelium, promoting neovascularization. However, despite their regenerative role, the number and function of EPC are severely affected under pathological conditions, being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 87 publications
(143 reference statements)
2
24
0
Order By: Relevance
“…Overall, these results reinforce the hypothesis that CACs-mediated revascularization is mainly achieved in a paracrine fashion. Thus, CAC's role is fundamental on the first days, when they participate in recruiting autologous progenitor cells [39][40][41] and promoting a mature and functional vascular network, in agreement with in vitro results where CACs secreted factors enhance ECFCs tubule formation [13,26,45].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Overall, these results reinforce the hypothesis that CACs-mediated revascularization is mainly achieved in a paracrine fashion. Thus, CAC's role is fundamental on the first days, when they participate in recruiting autologous progenitor cells [39][40][41] and promoting a mature and functional vascular network, in agreement with in vitro results where CACs secreted factors enhance ECFCs tubule formation [13,26,45].…”
Section: Discussionsupporting
confidence: 84%
“…As an alternative for those patients that are not suitable candidates for surgery, the use of pro-angiogenic cells such as endothelial progenitor cells (EPCs) has become a promising option, due to their potential to promote neovascularization in ischemic tissues. To date, two different subpopulations of EPCs have been described [ 9 , 10 , 11 , 12 , 13 ]: early EPCs, also called circulating angiogenic cells (CACs) or myeloid angiogenic cells, and late outgrowth EPCs or endothelial colony-forming cells (ECFCs). Both sets of cells have been tested to promote revascularization in ischemic diseases such as myocardial infarction or CLI [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MSCs secretomes are the most studied ones, secretomes of other stem/progenitor cells are also showing promising results. Very recently, we analyzed by a proteomic approach the secretome of CACs, identifying a significant number of angiogenic factors, and moreover, we demonstrated that incubation ex vivo of ECFCs with this secretome enhances ECFCs angiogenesis, in agreement with previous studies [ 77 , 110 ]. Moreover, ASCs secretome contains multiple angiogenic factors, which appear to promote, among others, survival, proliferation, and migration of ECs, as well as vasculogenesis [ 187 , 188 ].…”
Section: Strategies Derived From Cell Therapysupporting
confidence: 88%
“…Yoon et al evaluated this combined cell therapy, demonstrating a synergistic neovascularization involving several cytokines and matrix metalloproteinases (MMPs) [ 77 ]. Very recently, our group has also corroborated the potential of CACs to promote angiogenesis of ECFCs in vitro, and such effect was impaired under an atherosclerotic environment [ 110 ]. In the same way, different cell combinations have been tested.…”
Section: Angiogenic Cell Therapymentioning
confidence: 92%